Industry Evolution: New Technologies and New Firms - Darren Filson; April Mitchell Franco (Claremont McKenna College, Department of Economics, 1999)
This paper investigates the effects of employee mobility on industry evolution and technology diffusion by testing a dynamic industry equilibrium model introduced in Franco and Filson (1999). The model focuses on a particular type of employee mobility: researchers can leave existing firms and attempt to form new firms (spin-outs). The model has four testable results: First, spin-outs are an important source of entry. Second, spin-out founds come from firms with high know-how. Third, firms with high know-how are more likely to survive. Fourth, spin-outs whose parents have high know-how are more likely to survive. Using data from the rigid disk drive industry (1977-1997), we find support for the first three results and mixed support for the fourth.
Keywords: L10; L63; O31; 330; spin-off; industry dynamics; technological change; innovation; research and development